2022
DOI: 10.1515/chem-2022-0232
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, antidiabetic, and anticholinesterase potential of Chenopodium murale L. extracts using in vitro and in vivo approaches

Abstract: In this study, Chenopodium murale Linn. extracts have been evaluated for its in vitro antioxidant, enzyme inhibition, and in vivo neuropharmacological properties in streptozotocin (STZ)-induced memory impairment in rat model. First, the plant was subjected to extraction and fractionation, then quantitative phytochemical analysis was performed to estimate the major phytochemical groups in the extract where high amounts of phenolics and saponins were detected in crude and chloroform extract. The highest total ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 64 publications
1
4
0
Order By: Relevance
“…The ethanol extract demonstrated notable protein kinase inhibition that is consistent with results of this study. Our results were also in line with various studies including [37][38][39][40] suggesting ethanolic extracts of C. ambrosioides leaves contain potential phytochemicals that revealed different medicinal, anti-oxidant, and free radical scavenging properties proficiently. It's been widely accepted that flavonoids, a class of naturally occurring phenolic compounds, stand out as a prominent class among natural products.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The ethanol extract demonstrated notable protein kinase inhibition that is consistent with results of this study. Our results were also in line with various studies including [37][38][39][40] suggesting ethanolic extracts of C. ambrosioides leaves contain potential phytochemicals that revealed different medicinal, anti-oxidant, and free radical scavenging properties proficiently. It's been widely accepted that flavonoids, a class of naturally occurring phenolic compounds, stand out as a prominent class among natural products.…”
Section: Discussionsupporting
confidence: 91%
“…They found that C. murale treatment significantly protected the brain of the STZ-induced diabetic rats compared to neuronal damage caused by oxidative stress and improved cognitive dysfunction in behavioral studies which is consistent with our results of this study. [38] Nazir et al [54] investigated the antioxidant and cholinesterase inhibitory properties of Rosa moschata Herrm leaves and fruit methanolic extracts. Leaf extracts showed significantly higher anticholinesterase effects with IC50 values of 40 µg/ml (AChE) and 110 µg/ml (BChE), along with strong DPPH (IC50 = 360 µg/ml) and ABTS (IC50 = 105 µg/ml) radical scavenging capabilities than fruit extracts.…”
Section: Discussionmentioning
confidence: 99%
“…In the [5] and [10] studies, D.ambrosioides leaves were considered as potential source of anti‐bacterial and anti‐fungal effects, which probably could be explained by the presence of caryophyllene oxide who showed. For these therapeutic vertices, the leaves of the plant showed significant antioxidant activity at several scales, [11a] this could be explained by the presence of phytocompounds such as caryophyllene oxide which showed the highest inhibition towards Cytochrome P450 (PDBID : 1OG5), and NAD(P)H Oxidase (PDBID :2CDU). Other cardiovascular studies have been carried out, which were essentially based on the study of anti‐inflammatory, [13b] anti‐diabetic, [11a] antihypertensive [12] and vasodilating activity [14] of D.ambrosioides leaves, and significant therapeutic potentials of these leaves have been shown against several anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…For these therapeutic vertices, the leaves of the plant showed significant antioxidant activity at several scales, [11a] this could be explained by the presence of phytocompounds such as caryophyllene oxide which showed the highest inhibition towards Cytochrome P450 (PDBID : 1OG5), and NAD(P)H Oxidase (PDBID :2CDU). Other cardiovascular studies have been carried out, which were essentially based on the study of anti‐inflammatory, [13b] anti‐diabetic, [11a] antihypertensive [12] and vasodilating activity [14] of D.ambrosioides leaves, and significant therapeutic potentials of these leaves have been shown against several anomalies. Our results indicate that caryophyllene oxide, which is among the main phytochemical components, could be responsible for the observed experimental effects, showing the best affinity values for anti‐acterial (PDBID 4URM), anti‐diabetic (PDBID 2ZOX), anti‐inflammatory (PDBID 6COX), antihypertensive (PDBID 1R42 and 1UZF) and vasodilator receptors (PDBID 4RA4 and 4ZKF).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation